2022
DOI: 10.1177/09645284221078873
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture attenuates pulmonary vascular remodeling in a rat model of chronic obstructive pulmonary disease via the VEGF/PI3K/Akt pathway

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is characterized by airflow limitation that is not fully reversible. Pulmonary vascular remodeling is the main pathological feature of COPD. Vascular endothelial growth factor (VEGF), the key regulator of angiogenesis, mediates activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway, which regulates the proliferation and migration of vascular endothelial cells and plays important roles in pulmonary angiogenesis and remodeling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In addition, EA reduces pulmonary vascular remodeling in the COPD model via the PI3K/AKT signaling pathway. In spontaneously hypertensive rats, EA reduces phenotypic transformation of vascular smooth muscle cells via the PI3K/AKT signaling pathway [ 56 , 57 ]. Our results reveal that AKT and PIK3CA expression was upregulated in AMI myocardial tissues and that AKT1 was differentially expressed in MI-CTR and EA-treated MI rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EA reduces pulmonary vascular remodeling in the COPD model via the PI3K/AKT signaling pathway. In spontaneously hypertensive rats, EA reduces phenotypic transformation of vascular smooth muscle cells via the PI3K/AKT signaling pathway [ 56 , 57 ]. Our results reveal that AKT and PIK3CA expression was upregulated in AMI myocardial tissues and that AKT1 was differentially expressed in MI-CTR and EA-treated MI rats.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K transduction signal can promote the expression of proinflammatory cytokines (such as TNF-α and IL-6) by activating NF-κB downstream of AKT. Further phosphorylation of downstream substrates regulates different functions of cells, such as cell growth, metabolism and apoptosis [ [15] , [16] , [17] , [18] , [19] , [20] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Melatonin in the present study showed a significant decrease in VEGF and HIF-1α expression in lung tissue compared to the COPD group. Inhibition of HIF-1α and VEGF, whether at the transcriptional level or HIF-1α degradation, is the main target of Melatonin for inhibition of angiogenesis and oxidative stress especially under hypoxic conditions [ 45 , 68 , 75 , 86 , 88 ]. Other studies showed that depending on the surrounding microenvironment, Melatonin either stimulates or inhibits neovascularization by various mechanisms, producing different biological effects.…”
Section: Discussionmentioning
confidence: 99%